Niveles de ácido úrico, hemoglobina y hematocrito en nativos de las grandes alturas - Rojas S., Antonio (2000)
In order to determine the relationship between uric acid serum levels, hemoglobin and hematocrit in highlander native fellows; 40 blood samples of apparently healthy native fellows from Cerro de Pasco (4380 meters over sea level) were analyzed; and as reference, 25 samples of native fellows from Lima (150 m) were also analyzed, of both sexes and 34 year-old average. The results stated that there is a significant correlation between the levels of uric acid, hemoglobin and hematocrit, demonstrating that in high altitude the higher values of uric acid found would not be due to any pathology, but rather it is a normal present condition with high levels of hemoglobin and hematocrit which iscommon in highlander native fellows.